Perbandingan Penerjemahan Kosakata Arab pada Menu Windows dan macOS - Eldacca, Fayyaz; Hajidah, Gina Najjah (Journal of Arabic Language Studies and Teaching, 2025)
This research analyzes the Arabic translation of system settings vocabulary in two operating systems, Windows 10 and macOS Big Sur. The study aims to describe and compare the lexical differences arising from translating the English display language into Arabic. The data were obtained from screenshots of both systems and compiled into pairs of equivalent entries. Using a qualitative descriptive method, the study identifies the translation techniques and strategies applied in each operating system. The findings reveal that the most frequently used strategy is diversion, followed by loan translation, either with or without spelling modification. This study provides insights into Arabic localization in digital interfaces and highlights linguistic adaptation in technology translation.